Hypovitaminosis D Is A Risk Factor for Posterior Chain Muscular Injury in NCAA Division I Track And Field Athletes. Issue 7 (29th July 2019) - Lindsay, Adam; Jalali, Omid; Korber, Shane; Romano, Russ; Tibone, James E.; Weber, Alexander E.; Gamradt, Seth C.
Objectives: Currently little information is available in evaluating micronutrient requirements in elite athletes. Despite evidence that groups of NCAA athletes may be deficient in Vitamin D, no study to date has examined Vitamin D levels with respect to their predicative values for injuries to the 'posterior chain' musculature. The objective of this study was to evaluate the association between hypovitaminosis D and posterior chain injuries in NCAA Division I track and field athletes. Methods: After IRB approval, we evaluated data for men's and women's outdoor track and field teams from 2015-2018 at a large NCAA Division I athletics program. Vitamin D levels were drawn during pre-season annual physicals. The cutoff for hypovitaminosis D was set at 40 nmol/L. Demographic and athletic tenure data were recorded and analyzed, and competitive events were grouped into one of four categories: 1) running events, 2) jumping events, 3) throwing events, and 4) multiple event types. Student T tests, chi-squared tests, and multivariate logistic regression were performed. Results: The analysis consisted of 145 (58% female, 42% male) NCAA Division I track athletes. Eighty-five of the 145 athletes had hypovitaminosis D. A full breakdown of athlete characteristics by vitamin D status can be seen in Figure 1 and Table 1. Of the 145 athletes analyzed, 33 (22.7%) suffered a muscular injury to their posterior chain musculature. Multinomial logistic regression identified hypovitaminosis D as an independent risk factor for posterior chain injury (relative risk ratio: 3.23, p=0.016). Age, BMI, and event type were not predictive of a posterior chain injury. Of note, 4 (4.7%) athletes in the hypovitaminosis D group suffered multiple posterior chain injuries, with 2 (2.4%) athletes suffering 2 separate injuries and 2 (2.4%) athletes suffering 3 separate injuries. None of the athletes in the normal Vitamin D group suffered multiple posterior chain injuries. Conclusion: These results demonstrate that pre-season hypovitaminosis D is an independent risk factor for posterior chain muscular injury in NCAA division I track athletes. These data suggest that early detection of hypovitaminosis D may play a critical role in injury prevention for these athletes. Table 1. Athlete characteristics by Vitamin D status Vit D 10-40 Vit D >40 p-value Count (% of total) 85 (58.6%) 60 (41.4%) Age 20.3 ± 0.23 20.7 ± 0.28 0.31 BMI 22.8 ± .49 22.6 ± .58 0.829 Sex M: 38 F: 47 M: 22 F: 38 0.333 Race White: 16 (34.04%) Black: 44 (80.0%) Hispanic:0 (0.00%) Asian: 1 (50.00%) Multi:26 (63.64%) White: 31 (65.96%) Black: 11 (20.00%) Hispanic: 1 (100.00%) Asian:1 (50.00%) Multi: 12 (36.36%) <0.001 Event Type Running: 60 (70.6%) Jumping Throwing: 11 (12.94%) Throwing: 8 (9.41%) Multiple event types: 6 (7.06%) Running: 44 (74.58%) Jumping: 5 (8.47%) Throwing: 9 (15.25%) Multiple event types: 1 (1.69%) 0.287